The evolution of the CTO-PCI landscape in Belgium and Luxembourg: a four-year appraisal. Issue 10 (5th November 2021) - Eertmans, Ward; Kayaert, Peter; Bennett, Johan; Ungureanu, Claudiu; Bataille, Yoann; Saad, Georges; Haine, Steven; Coussement, Patrick; Pereira, Bruno; Agostoni, Pierfrancesco; Janssens, Luc; Vandeloo, Bert; et al.
Abstract: Background: To chart the evolution of the CTO-PCI landscape in Belgium and Luxembourg, the Belgian Working Group on Chronic Total Occlusions (BWGCTO) was established in 2016. Methods: Between May 2016 and December 2019, patients undergoing a CTO-PCI treatment were prospectively and consecutively enrolled. Twenty-one centres in Belgium and one in Luxembourg participated. Individual operators had mixed levels of expertise in treating CTO lesions. Demographic, angiographic, procedural parameters and incidence of major adverse cardiac and cerebrovascular events (MACCE) were systematically registered. Results: Over a four-year enrolment period, 1832 procedures were performed in 1733 patients achieving technical success in 1474 cases (80%), with an in-hospital MACCE rate of 2.3%. Fifty-nine (3%) cases were re-attempt procedures of which 41 (69%) were successful. High-volume centres treated more complex lesions (mean J-CTO score: 2.15 ± 1.21) as compared to intermediate (mean J-CTO score: 1.72 ± 1.23; p < 0.001) and low-volume centres (mean J-CTO score: 0.99 ± 1.21; p = 0.002). Despite this, success rates did not differ between centres ( p = 0.461). Overall success rates did not differ over time ( p = 0.810). High-volume centres progressively tackled more complex CTOs while keeping success rates stable. In all centres, the most applied strategy was antegrade wire escalation (83%). High-volume centres more often successfully applied antegrade dissection and re-entry and retrograde techniques in lesions with higher complexity. Conclusion: With variable experience levels, operators treated CTOs with high success and relatively few complications. Although AWE remains the most used technique, it is paramount for operators to be skilled in all contemporary techniques in order to be successful in more complex CTOs.